Exploring the Effects of Dynamic Assessment on Improving Iranian Quran Learners’ Recitation Performance - Afsheen Rezai; Ehsan Namaziandost; Ayub Amraei (Critical Literary Studies, 2023)
Although Dynamic Assessment (DA), rooted in Vygotsky’s (1978) Zone of Proximal Development (ZPD) notion, has been extensively researched in teaching English as a foreign language, it has remained largely unexplored in teaching Arabic as a foreign language. To bridge this long-lasting gap, this study purports to investigate the effects of DA on improving Iranian Quran learners’ recitation performance. For this purpose, two intact grade 7 classes were selected at a public high school in Borujerd city, Iran, and were assigned randomly as DA group (n=21) and non-DA group (n=23). Later, they went through a pre-test, intervention (offered based on the principles and procedures of DA for the DA group and held in 15 sessions), immediate post-test, and delayed post-test. The collected data were analyzed through a one-way ANCOVA. Findings documented that the DA group outperformed the non-DA group on the immediate post-test. Additionally, the results evidenced that the DA group outweighed the control group on the delayed post-test. The study ends with proposing some implications in consistent with the tenets of Sociocultural theory.